Yolo Deep Learning Model Based Algorithm for Object Detection - Kaur, Amandeep; Kaur, Deepinder (International Journal of Computer Sciences and Engineering, 2020)
With the growth of deep learning and digital image processing, it is require knowing about the facts of deep learning. Deep learning is major factor of object detection. In existing research R-CNN algorithm used for detect the objects from an image while in this proposed research method we are using YOLO (you only look once) algorithm to detect the different objects in a single image. This is less time consuming because we only recognize a image once and we detect the whole objects in an image.